2015
DOI: 10.3748/wjg.v21.i33.9827
|View full text |Cite
|
Sign up to set email alerts
|

Giant liposarcoma of the esophagus: A case report

Abstract: Liposarcomas rarely develop in the aerodigestive tract. Here, we present a primary esophageal liposarcoma that was discovered between the T3 and T7 levels of the esophagus during right pleural exploration of a 51-year-old male patient. The patient had presented with non-specific symptoms, including progressive dysphagia over the previous 6 mo, without complaints of chest or epigastric pain, regurgitation, or weight loss. A radical three-hole esophagectomy was performed. The tumor was extremely large (14 cm × 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The standard of care for giant esophageal polyps is surgical resection, which can be directed by different techniques; including an aggressive open cervical approach, radical three-hole esophagectomy, or local endoscopic resection[8,9]. Since in our case the endoscopic ultrasound identified a single proximal stalk without a significant feeding vessel, trans oral endoscopic resection was pursued; making sure completeness was achieved by examining margins of specimen to be uninvolved, as cases of reoccurrence after inadequate resection have been reported[2,5].…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care for giant esophageal polyps is surgical resection, which can be directed by different techniques; including an aggressive open cervical approach, radical three-hole esophagectomy, or local endoscopic resection[8,9]. Since in our case the endoscopic ultrasound identified a single proximal stalk without a significant feeding vessel, trans oral endoscopic resection was pursued; making sure completeness was achieved by examining margins of specimen to be uninvolved, as cases of reoccurrence after inadequate resection have been reported[2,5].…”
Section: Discussionmentioning
confidence: 99%
“…A giant thoracic neoplasm is extremely rare and has only occasionally been cited in the literature, usually in single cases . To our knowledge, only one previous has reported conclusions after surgical treatment .…”
Section: Discussionmentioning
confidence: 94%
“…A giant thoracic neoplasm is extremely rare and has only occasionally been cited in the literature, usually in single cases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To our knowledge, only one previous has reported conclusions after surgical treatment. 26 Our retrospective study of 45 patients showed the complexity and heterogeneity of giant thoracic neoplasm through clinical characteristics, imaging manifestations, surgical management, pathology, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liposarcoma in the gastrointestinal tract is an uncommonpathology especially in the oesophagus (1.2% to 1.5% of all gastrointestinal lipomas) [[6], [7], [8]]. Only 42 cases was reported in the literature [9,2].…”
Section: Discussionmentioning
confidence: 99%